2017
DOI: 10.3390/environments4020040
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Aseptic Culture System and Analysis of the Effective Growth Conditions for Eleocharis acicularis Ramets for Use in Phytoremediation

Abstract: Eleocharis acicularis, an aquatic macrophyte of the Cyperaceae family, has been shown to accumulate multiple heavy metals and has great potential for use in the phytoremediation of contaminated soil and water. To investigate the mechanism of accumulation of heavy metals in E. acicularis while excluding biotic and abiotic environmental effects and to acquire homogenous and sufficient populations of E. acicularis, we established an aseptic culture system and analyzed the applicability of this species for phytore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Table 2 compares the results obtained in this study with those of similar previous studies reported by Ha et al 15 and Sato et al 31 Ha et al 15 used initial indium feeds of 0.1, 0.2, and 0.4 mg/L and reported a maximum uptake of 0.83 mg/g dry weight (roots and shoots) by E. acicularis. A similar study was conducted by Sato et al 31 with an increased feed concentration (38 mg/L), which demonstrated a significantly higher accumulation reaching 17.8 mg/g with a BCF of 468. In our study, indium accumulation in dry biomass was astonishingly high, although the calculated BCF values were approximately half of those reported by Sato et al 31 Thus, fresh and pyrolyzed plant biomass samples were subjected to extensive EDS analyses, as discussed further in the text.…”
Section: ■ Experimental Sectionsupporting
confidence: 83%
See 1 more Smart Citation
“…Table 2 compares the results obtained in this study with those of similar previous studies reported by Ha et al 15 and Sato et al 31 Ha et al 15 used initial indium feeds of 0.1, 0.2, and 0.4 mg/L and reported a maximum uptake of 0.83 mg/g dry weight (roots and shoots) by E. acicularis. A similar study was conducted by Sato et al 31 with an increased feed concentration (38 mg/L), which demonstrated a significantly higher accumulation reaching 17.8 mg/g with a BCF of 468. In our study, indium accumulation in dry biomass was astonishingly high, although the calculated BCF values were approximately half of those reported by Sato et al 31 Thus, fresh and pyrolyzed plant biomass samples were subjected to extensive EDS analyses, as discussed further in the text.…”
Section: ■ Experimental Sectionsupporting
confidence: 83%
“…A similar study was conducted by Sato et al 31 with an increased feed concentration (38 mg/L), which demonstrated a significantly higher accumulation reaching 17.8 mg/g with a BCF of 468. In our study, indium accumulation in dry biomass was astonishingly high, although the calculated BCF values were approximately half of those reported by Sato et al 31 Thus, fresh and pyrolyzed plant biomass samples were subjected to extensive EDS analyses, as discussed further in the text. Notably, we used the highest indium feed concentrations reported to date, which were orders of magnitude higher than those reported in the literature.…”
Section: ■ Experimental Sectionsupporting
confidence: 72%
“…There has likely been a central debate regarding the role of Si for mediating metal stress [9,33]. Many studies stated the role of Si in diminishing plants' metal absorption [25,27,34], while some others reported a co-absorption of Si and metals into plants [24,32]. In our study, it was obvious that Si favored the absorption of heavy metals (except In and Tl) into E. acicularis (Table 1).…”
Section: Combined Effects Of E Acicularis and Dissolved Si On The Removal Of Heavy Metalsmentioning
confidence: 49%
“…longiseta Svenson is an emergent herbaceous perennial with a worldwide distribution [19]. This species has been reported to accumulate multiple metals from mine drainage, water, and sediment, and shows a great potential for phytoremediation [12,[20][21][22][23][24][25][26]. However, currently, there is no available information regarding the simultaneous accumulation of rare metals (i.e., gallium (Ga) and thallium (Tl)) in E. acicularis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation